Zootherapy in archaeology: the case of the fallow deer (Dama dama dama) - Miller, Holly; Sykes, Naomi (BioOne, 2016)
The abundant anthropological and historical evidence for animal-based medicine, or zootherapy, suggests that animals are, and have always been, perceived as important components in maintaining human health and well-being. Despite being interwoven into every aspect of life, from food medicines to ritual practice and everyday human-animal interactions, zootherapies are widely considered invisible in the archaeological record, perhaps because of their organic nature, the method of remedy preparation, or potentially because of their sheer ubiquity. An alternative explanation is that archaeologists are just not viewing the evidence through an appropriate theoretical lens. This article sets out to examine whether archaeologists might make a greater contribution to our understanding of ancient zootherapy. As a case study, it draws particularly on evidence pertaining to the European fallow deer (Dama dama dama) an exotic species that is well represented in classical mythology and iconography and appears to have been attributed with magico-religious medicinal qualities. Indeed, here we argue that their perceived magico-medicinal value may even have been the prime mover in their human-instigated spread across Europe.